Perspectives for the Use of Social Media in e-Pharmamarketing - Syrkiewicz-Świtała, Magdalena; Romaniuk, Piotr; Ptak, Ewa (Frontiers in Pharmacology, 2016)
The Internet has become a common and global medium. It contains vast information resources and a wide range of communication instruments. One of the communication channels are social media, which increasingly are also used in the business field. Social media combined with mobile technology introduced new challenges to marketing activity. This trend is also observed on specific and highly regulated drug market. The aim of this article is to describe the perspectives for the use of social media in e-pharmamarketing. We find that this require personalized communication, the use of online promotion tools, in order to perform advertising in contact with a demanding client. Currently pharmaceutical companies use social media to communicate basic information on their life, but they still do not appreciate it sufficiently as a tool to build the image of company or products. It is therefore considered that these companies should attach greater importance to the presence in this type of media, especially in the light of dynamic changes in the way people communicate.